2007
DOI: 10.1074/jbc.m609335200
|View full text |Cite
|
Sign up to set email alerts
|

αvβ5 Integrin Sustains Growth of Human Pre-B Cells through an RGD-independent Interaction with a Basic Domain of the CD23 Protein

Abstract: CD23 is a type II transmembrane glycoprotein synthesized by hematopoietic cells that has biological activity in both membrane-bound and freely soluble forms, acting via a number of receptors, including integrins. We demonstrate here that soluble CD23 (sCD23) sustains growth of human B cell precursors via an RGD-independent interaction with the ␣v␤5 integrin. The integrin recognizes a tripeptide motif in a small disulfidebonded loop at the N terminus of the lectin head region of CD23, centered around Arg 172 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 40 publications
0
26
0
Order By: Relevance
“…It is important to note that FCER2 gene products may exert growth factor activity for B cells (Borland et al, 2007) and that NR4A1 induces apoptosis in response to a broad range of stimuli including PMA and apoptotic BCR signalling (Mapara et al, 1995;Li et al, 2000). Taking into consideration that NOTCH interferes with the apoptotic function of NR4A1 (Lee et al, 2002), the observed upregulation of NR4A1 in response to PMA might mechanistically explain why PMA enhances the apoptotic effect of gliotoxin-mediated NOTCH2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that FCER2 gene products may exert growth factor activity for B cells (Borland et al, 2007) and that NR4A1 induces apoptosis in response to a broad range of stimuli including PMA and apoptotic BCR signalling (Mapara et al, 1995;Li et al, 2000). Taking into consideration that NOTCH interferes with the apoptotic function of NR4A1 (Lee et al, 2002), the observed upregulation of NR4A1 in response to PMA might mechanistically explain why PMA enhances the apoptotic effect of gliotoxin-mediated NOTCH2 inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…1 The interaction between soluble CD23 (sCD23) and the integrin avb5 sustains growth of human pre-B cell lines derived from ALL patients. 2,3 Human CD23, a 45-kDa type II transmembrane glycoprotein, can be cleaved from the cell surface to release a range of sCD23 proteins with cytokinelike activities. The cytokine-like activities include promoting the release of cytokines from monocytic cells, mediated by the aMb2, aXb2 4,5 and avb3 integrins, 6 and influencing the survival and differentiation of centrocytes by binding to CD21.…”
Section: Introductionmentioning
confidence: 99%
“…11 The avb5 integrin, a member of the vitronectin receptor family, is expressed by bone marrow B-cell precursors. 2 The vitronectin receptor family members comprise the av chain in non-covalent association with one of five b-subunits (b1, b3, b5, b6 and b8) and bind a broad spectrum of ligands, including fibrinogen, fibronectin and vitronectin, typically by the recognition of arg-gly-asp motifs. [12][13][14] Vitronectin receptors have diverse roles in cell adhesion, migration and survival and are implicated in the growth of a number of cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations